Aging Prisoners: A Brief Report of Key Legal and Policy Dilemmas - Doron, Israel Issi; Love, Helene (International Journal of Criminology and Sociology, 2013)
Background: The social phenomenon of the aging of the prison population has raised various legal and policy challenges. Objective: The goal of this brief report is to describe the current key legal-policy dilemmas in this field. Methods: A computerized search for legal documents, articles and studies using relevant key words was conducted in computerized databases. Results: Five key dilemmas were found: (1) Early and compassionate release of older prisoners; (2) Segregation or integration of older prisoners; (3) Heaven or hell? The meaning of imprisonment in old age; (4) Fixed v. tailored sentences to older offenders; and (5) Is prison the right place to send older offenders? Conclusion: Evidence regarding the unique socio-medical needs of older prisoners does not provide easy or simple answers to the legal-policy dilemmas in this field. Hence, as of today, the scholarly discussions in this field seem to be more normative (what "should" be the solution) rather than empirical (what "is" the evidence-based solution). Therefore, more empirical evidence is needed in order to design old-age based legal-policies towards older prisoners.